Branebrutinib (BMS-986195), a Bruton’s Tyrosine Kinase Inhibitor, Resensitizes P-Glycoprotein-Overexpressing Multidrug-Resistant Cancer Cells to Chemotherapeutic Agents - Wu, Chung-Pu; Murakami, Megumi; Wu, Yu-Shan; Chi, Ya-Chen; Hsiao, Sung-Han; Huang, Yang-Hui; Hung, Tai-Ho; Ambudkar, Suresh V. (Frontiers in Cell and Developmental Biology, 2021)
The overexpression of P-glycoprotein (P-gp/ABCB1), an ATP-binding cassette (ABC) drug transporter, often contributes to the development of multidrug resistance (MDR) in cancer cells. P-gp mediates the ATP hydrolysis-dependent efflux of a wide range of chemotherapeutic agents out of cancer cells, thereby reducing the intracellular drug accumulation and decreasing the chemosensitivity of these multidrug-resistant cancer cells. Previous studies have reported that certain tyrosine kinase inhibitors (TKIs) could reverse MDR mediated by P-gp, while some TKIs are transported by P-gp. In the present work, we explored the prospect of repositioning branebrutinib (BMS-986195), a highly selective inhibitor of Bruton's tyrosine kinase (BTK), to resensitize P-gp-overexpressing multidrug-resistant cancer cells to chemotherapeutic agents. Our results demonstrated that branebrutinib is capable of reversing P-gp-mediated MDR at sub-toxic concentrations, most likely by directly inhibiting the drug transport function of P-gp. It stimulates ATPase activity of P-gp in a concentration manner and the in silico docking analysis of branebrutinib binding to the substrate-binding pocket of P-gp further supports our findings. In addition, we found that P-gp-overexpressing multidrug-resistant cell lines and their respective drug-sensitive parental cell lines are equally sensitive to branebrutinib, suggesting that it is unlikely that the overexpression of P-gp in cancer cells plays a significant role in reduced susceptibility or resistance to branebrutinib. In summary, we discovered an additional pharmacological action of branebrutinib against the activity of P-gp, which should be investigated further in future drug combination studies.